The impact of the US unilateralism on international law: the situation of jus ad bellum after September 11 - Yüce, Merve. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2007., 2007)
This study aims at addressing the question of what can be the long-term implications of the US unilateralism on international law especially on jus ad bellum with regard to the United States’ hegemonic position in the system. Even though an endless debate over the legality of the US actions seems in vain, to answer this question is only possible by a detailed analysis of the US justifications in resorting to force after September 11 attacks. Considering the historical continuity of the United States’ unilateralist policies in post cold war epoch, such an analysis interrogating the US arguments can reveal the comprehensive consequences of these policies on international law. To achieve this goal, this study will start with an introduction to the notion of American unilateralism by examining its instances in trade, environmental and humanitarian issues. Then, America’s war on terrorism as well as the surrounding concepts such as rogue state, axis of evil and succeeding operations to Afghanistan and Iraq will be evaluated within the present legal framework. Many of the authors who have written on the legal issues arising out of the United States’ operations against Afghanistan and Iraq usually concentrate on the validity of the US justifications without considering the long term implications of these justifications. However, the United States’ arguments certainly deserve a closer look with regard to the fact that the United States’ unilateralist stance towards international legal body and norms governing the use of force might be seen as an indicator of American efforts to expand existing limits of normative framework of law on behalf of its policy ends. As a consequence, it might be possible to understand how the US actions trigger the transformative or devastating- changes on the existing norms of international law.
Keywords: United States -- Politics and government -- 2001-; United States -- Foreign relations -- 2001-